2022
DOI: 10.3389/fcvm.2022.875434
|View full text |Cite
|
Sign up to set email alerts
|

Key ferroptosis-related genes in abdominal aortic aneurysm formation and rupture as determined by combining bioinformatics techniques

Abstract: ObjectivesAbdominal aortic aneurysm (AAA) is a cardiovascular disease with high mortality and pathogenesis closely related to various cell death types, e.g., autophagy, apoptosis and pyroptosis. However, the association between AAA and ferroptosis is unknown.MethodsGSE57691 and GSE98278 dataset were obtained from the Gene Expression Omnibus database, and a ferroptosis-related gene (FRG) set was downloaded from the FerrDb database. These data were normalized, and ferroptosis-related differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Previous data have indicated that iron ion levels are elevated in arterial tissue in AAA, and that the process of AAA is exacerbated by oxidative stress and inflammatory responses due to iron overload 22 . In a recently published article, SLC7A11 and GPX4 gene expressions were shown to be expressed in diseased vascular tissue and normal tissue in patients with AAA and showed some correlation with tissue infiltrating immune cells 9 . In addition, it has been reported that abnormal expression of SLC7A11/GPX4 genes in locally infiltrating macrophages in the development of AAA leads to an oxidative imbalance and enhanced migration of macrophages, which promotes the progression of AAA 23 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous data have indicated that iron ion levels are elevated in arterial tissue in AAA, and that the process of AAA is exacerbated by oxidative stress and inflammatory responses due to iron overload 22 . In a recently published article, SLC7A11 and GPX4 gene expressions were shown to be expressed in diseased vascular tissue and normal tissue in patients with AAA and showed some correlation with tissue infiltrating immune cells 9 . In addition, it has been reported that abnormal expression of SLC7A11/GPX4 genes in locally infiltrating macrophages in the development of AAA leads to an oxidative imbalance and enhanced migration of macrophages, which promotes the progression of AAA 23 .…”
Section: Discussionmentioning
confidence: 98%
“…22 In a recently published article, SLC7A11 and GPX4 gene expressions were shown to be expressed in diseased vascular tissue and normal tissue in patients with AAA and showed some correlation with tissue infiltrating immune cells. 9 In addition, it has been reported that abnormal expression of SLC7A11/GPX4 genes in locally infiltrating macrophages in the development of AAA leads to an oxidative imbalance and enhanced migration of macrophages, which promotes the progression of AAA. 23 Previous studies have found that AngII plays an important role in the initiation, formation, and rupture of AAA, which may be related to macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GP90 activated the innate immune response in combination with CP, and also involved the NOD-like receptor signalling pathway, Toll-like receptor signalling pathway, and T cell receptor signalling pathway, and plays a role in ferroptosis by regulating oxidative stress. 46 Further study will address the effect of GP90 on the immune function in CP-treated C26 carcinoma tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%